Cocaine trafficking in Latin America : EU and US policy responses - Fukumi, Sayaka, 1973- (Aldershot, Hants, England ; Burlington, VT : Ashgate, 2008)
"The European Union and the United States have identified Latin American cocaine trafficking as a security threat, but their policy responses to it have differed. This book examines the way in which the EU and US have conceptualized this threat. Furthermore, it explores the impact of cocaine trafficking on four state functions: economic, political, public order, and diplomatic, in order to explain why it has become 'securitized'."--BOOK JACKET.
Introduction -- Securitisation and drug control policy : theoretical frameworks -- The "securitisation" of cocaine trafficking in the European Union -- The "securitisation" of cocaine trafficking in the United States -- EU drug control policy towards the Andes -- US drug control policy towards the Andes -- Plan Colombia : an attempt at multinational co-operation -- Conclusion.
Includes bibliographical references (p. [226]-278) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: National security -- United States; National security -- European Union countries; Cocaine industry -- Latin America; Drug traffic -- Latin America; Transnational crime -- Government policy -- United States; Transnational crime -- Government policy -- European Union countries; Drug control -- United States; Drug control -- European Union countries; Electronic books